GRNOPC1: the world''s first embryonic stem cell-derived therapy. (November 2011) - Lebkowski, Jane
Interview with Jane Lebkowski Geron''s Chief Scientific Officer, Jane Lebkowski, discusses the long road to clinical trials and the next steps for GRNOPC1. The long-awaited clinical trial of Geron''s GRNOPC1 therapy for spinal cord injury has been one of the biggest stories in regenerative medicine over the past few years. The trial initially received the go-ahead from the US FDA in early 2009, but was put on clinical hold soon afterwards when an increased frequency of cysts was found in an animal experiment. Revision in release criteria and additional prospective animal studies allayed these concerns and the clinical hold was finally lifted in June 2010. The Phase I clinical trial enrolled its first patient in October 2010. As the world''s first human trial of an embryonic stem cell-derived therapy, the trial has generated a huge amount of attention.